2019
DOI: 10.1159/000502287
|View full text |Cite
|
Sign up to set email alerts
|

Dual Therapy with Vonoprazan and Amoxicillin Is as Effective as Triple Therapy with Vonoprazan, Amoxicillin and Clarithromycin for Eradication of Helicobacter pylori

Abstract: Backgrounds/Aims: Vonoprazan (VPZ) is the first clinically available potassium competitive acid blocker. This class of agents provides faster and more potent acid inhibition than proton pump inhibitors. Most strains of Helicobacter pylori are sensitive to amoxicillin. We hypothesized that dual therapy with VPZ and amoxicillin would provide the sufficient eradication rate for H. pylori infection. To evaluate this, we compared the eradication rate by the dual VPZ/amoxicillin therapy with that by the standard tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
129
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 44 publications
2
129
0
3
Order By: Relevance
“…We read the manuscript written by Suzuki et al 1 with interest. They reported that the eradication rate of Helicobacter pylori attained by the dual therapy with vonoprazan and amoxicillin (VA-Dual) was almost the same as that attained by the triple therapy with vonoprazan, amoxicillin and clarithromycin (VAC-Triple), as previously reported by us 2. The most interesting point in this paper was that the VA-Dual therapy was superior to the VAC-Triple therapy in eradicating the clarithromycin-resistant strains of H. pylori .…”
supporting
confidence: 77%
“…We read the manuscript written by Suzuki et al 1 with interest. They reported that the eradication rate of Helicobacter pylori attained by the dual therapy with vonoprazan and amoxicillin (VA-Dual) was almost the same as that attained by the triple therapy with vonoprazan, amoxicillin and clarithromycin (VAC-Triple), as previously reported by us 2. The most interesting point in this paper was that the VA-Dual therapy was superior to the VAC-Triple therapy in eradicating the clarithromycin-resistant strains of H. pylori .…”
supporting
confidence: 77%
“…Another key parameter to the success of a dual therapy regimen is to maintain steady AMO plasma concentrations above the MIC level for its bactericidal effect against H. pylori . The results of a retrospective study in which dual therapy (vonoprazan 20 mg twice daily and AMO 500 mg three times daily for 7 days) provided an eradication rate of 93% as first-line treatment39 suggested that high administration frequency of AMO could improve the eradication rate in vonoprazan-based dual therapy to values similar to those of high-dose and high-frequency AMO–PPI dual therapy. Thus, further adjustments in the administration frequency and dose of AMO are necessary to improve the eradication effect of the VA-dual therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vonoprazan, a potassium‐competitive acid blocker, has recently been approved to treat H pylori infection, and is regarded as a faster, more potent, and more long‐acting agent than traditional PPIs 36,37 . A retrospective study conducted in a small sample from Japan showed that 7‐day vonoprazan 20 mg bid and amoxicillin 500 mg tid dual therapy have achieved an eradication rate of 92.9% in ITT analysis 38 . Thus, it is imperative to conduct more clinical trials to assess the efficacy of dual therapy by replacing the traditional PPIs with vonoprazan.…”
Section: Discussionmentioning
confidence: 99%